Bandgap engineering and thermodynamic stability of oxyhalide and chalcohalide antiperovskites. Issue 23 (1st December 2021) - Liu, Zhiyang; Mi, Ruixiang; Ji, Guoqi; Liu, Yingmeng; Fu, Pengfei; Hu, Sanlue; Xia, Bing; Xiao, Zewen
Abstract: Like ABX3 halide perovskites, A3 YX antiperovskites also have high symmetry and high electronic dimensionality and thus are expected to hold the promise of producing excellent optoelectronic properties. In this work, we explore the optoelectronic-relevant properties of oxyhalide and chalcohalide antiperovskites A3 YX through a combination of density functional theory calculations, chemical synthesis, and material characterizations, with a particular focus on bandgap engineering and thermodynamic stability. It is found that the conduction band minimum and valence band maximum of these antiperovskites are contributed mainly by the cations at the octahedral corners and the anions at the octahedral centers, respectively. In contrast, the halogen anions at the cuboctahedral voids contribute little to the band edges. As a result, element substitutions at the octahedral corners and centers can effectively engineer the bandgaps, whereas those at the cuboctahedral voids have limited influence on the bandgap. Further, it is found that the thermodynamic stability of these antiperovskites depends strongly on the constituent ions, e.g., the thermodynamic stability decreases significantly as the Y anion changes from O to S and Se. Our results provide critical insights into the bandgap properties and thermodynamic stability of A3 YX oxyhalide and chalcohalide antiperovskites for potential optoelectronic applications.